Enhancing Psychological Well-Being With Mindfulness Therapy: A Review of Meta-Analysis - Hastuti, Fajar Ayu; Yudiarso, Ananta (Jurnal Sains Psikologi, 2024)
Psychological well-being is a critical dimension of individual mental health. This study aims to assess the effectiveness of mindfulness therapy in enhancing psychological well-being through a meta-analysis conducted with Jamovi 2.3.62. The analysis included 11 experiment studies, with 304 participants in the experimental group and 302 in the control group. The meta-analysis yielded an effect size of 2.00 (95% CI = 1.015 to 2.987), indicating mindfulness’s large and significant impact. The I² statistic of 96.02% also reveals high heterogeneity among the studies. These results confirm that mindfulness therapy is potent for improving psychological well-being.